An analysis of performance measurement system used in Indonesia local government - Murti, Ridho Bayu; Mahmudi, Mahmudi; Nurfauziya, Ahada (Journal of Contemporary Accounting, 2021)
This study examines the antecedents and consequences of the use of the performance measurement system of local government. It aimed to investigate the effect of organizational culture, external pressures, and leadership commitment using a performance measurement system. It also further investigates whether the use of a performance measurement system affects public accountability. The data were collected by distributing a questionnaire to the local government staff. The sample of this study was civil servants of the Special Region of Yogyakarta. There were 95 respondents in this study. In analyzing the data, multiple linear regression was used. The results indicate that organizational culture, external pressures, and leadership commitments significantly affected the performance measurement system. It also found that using a performance measurement system had a significant positive effect on public accountability.